A review on parametric and nonparametric empirical likelihood method based on interval-censored data - Zainudin, Norazelah; Elfaki, Faiz Ahmed Mohamed; Yeakub Ali , Mohammad (Sci.Int.(Lahore), 2014)

(untitled)
This paper shall review on the estimation of distribution function for both parametric and nonparametric empirical likelihood method. The focus of this review is on empirical likelihood regression method behavior on censored data and how those methods affect the result of the simulation studies. Moreover, we looking into the case which is involve the partly interval censored data.